SYNTHESIS AND PROPERTIES OF 3-(4-ARYL-5-(ARYLCARBOXAMIDO)THIAZOLE-2-YL)CHROMONES: DOI: https://doi.org/10.17721/1728-2209.2025.1(60).4 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2025)
Background. The wide spectrum of biological activity of 3-thiazolylchromones and their low toxicity determines the relevance of research on synthesis and study of their chemical and biological properties. Previously, we developed a method for the synthesis of α-thiazolyl-2,4-dihydroxyacetophenones based on substituted resorcinols and thiazolylacetonitriles and showed the possibility of their cyclization into 3-thiazolylchromones. The aim of this study was the synthesis of new derivatives of 3-thiazolylchromones containing additional functional group in the thiazole cycle.Heterocyclization as a method of 3-(4-aryl-5-(arylcarboxamido)thiazol-2-yl)chromones synthesis; Mannich reaction, spectral characteristics of synthesized substances.Methods. Organic synthesis of 3-(4-aryl-5-(arylcarboxamido)thiazol-2-yl)chromone derivatives; characterization of the synthesized substances using 1H NMR and IR spectroscopy.Results. Based on 4-ethylresorcinol and {4-aryl-5-(arylcarboxamido)thiazol-2-yl]acetonitriles, a number of α-[4-aryl-5-(arylcarboxamido)thiazol-2-yl)]acetophenones were synthesized and their further heterocyclization with ethyl orthoformate and carboxylic acid anhydrides led to new derivatives of 3-(thiazol-2-yl)chromones, namely 2-(un)substituted 3-(4-aryl-5-(arylcarboxamido)thiazol-2-yl)chromones. The aminomethylation reaction with bisdimethylaminomethane with the formation of the corresponding Mannich base was investigated.Conclusions. It was established that [4-aryl-5-(arylcarboxamido)thiazol-2-yl]acetoacetonitriles successfully react with resorcinols under the modified conditions of the Houben–Hoesch reaction with the formation of α-[4-aryl-5-(arylcarboxamido)thiazol-2-yl )]acetophenones, which are key synthons for further heterocyclization into the corresponding 3-(thiazol-2-yl)chromones. It was shown that the Vilsmeier reaction was more successful than the Venkataraman synthesis for obtaining chromatographically pure terminal chromones. Modification of the corresponding chromones by aminomethylation is a promising direction for the synthesis of biologically active compounds.
Keywords: [4-aryl-5-(arylcarboxamido)thiazol-2-yl]acetoacetonitriles, α-[4-aryl-5-(arylcarboxamido)thiazol-2-yl]acetophenones, 3-(4- aryl-5-(arylcarboxamido)thiazol-2-yl)chromones, heterocyclization, Mannich reaction.